Penggunaan telemarketing sebagai media dalam meningkatkan Jumlah nasabah asuransi jiwa dan kesehatan (Faculty of Communications Science, Dr. Soetomo University, 2022)
In the insurance business world, customer convenience is the utmost priority. Service quality is the most important factor to be able to compete in the insurance service industry sector. Continuous innovation can certainly be an attraction for customers or prospective customers. PT AXA Financial Indonesia is no exception. AXA Financial Indonesia has a motto of customer first, where the customer is the most important thing. This is inseparable from the marketing strategy designed to be competitive and of course to invite more people to join in using the insurance products offered. This study uses descriptive qualitative methods with data collection techniques through observation and in-depth interviews with related informants. The theory used is the theory of marketing communication. This study aims to see what strategies are used, the stages, and the final results of whether the marketing strategy through telemarketing used can increase the number of customers and company income. Not only that, but this research also looks at the obstacles in the marketing process through telemarketing.